EMPLOYEE RELATIONS DALAM PRODUKTIVITAS KERJA (STUDI FENOMENOLOGI PADA PERUSAHAAN MAKACIKI) - Vashya Tiara Iskandar (2020)
The challenge for online businesses is strong competitive power due to price transparency and the presence of business rivals within a click of the mouse. Consumers are faced with several choices with variations in price and product quality, each of which is produced by the seller. It is therefore necessary to process human resources in order to be adaptive, creative and innovative. This study aims to identify employee relations in work productivity pursued by one of the online shop companies, Makaciki. Where the company is filled with the dominance of employees aged 18-27 years. In addition, the educational background of employees is still minimal, both formal and non-formal. The purpose of this study is to analyze and describe the employee relations applied by Makaciki as an online shop. By using qualitative research methods. Data collection techniques used was interviews and observation. Based on the results of the study, applied employee relations is cooperation by helping each other regardless of the position they have. Makaciki also conducts support activities for employees such as seminars, employee of the month, stand-up meetings and sign-to-do lists. As well as holding activities outside the formalities such as farewell parties, birthday cellebration, and Friday Koran. So with the situation of young human resources and minimal experience can be balanced with the existence of these activities for work productivity.